1965
DOI: 10.1128/jb.89.6.1443-1447.1965
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Properties of Some L Forms Derived From Gram-Positive and Gram-Negative Bacteria

Abstract: Sweden), AND HANS GYLLANG. Metabolic properties of some L forms derived from gram-positive and gram-negative bacteria. J. Bacteriol. 89:1443-1447. 1965.-L forms of two gram-positive bacteria, a staphylococcus and a diphtheroid, were found to be devoid of catalase and cytochromes, whereas the normal bacteria from which these L forms were derived contained large amounts of these enzymes. On the other hand, L forms of a gram-negative bacterium, Proteus mirabilis, contained the same cytochromes as normal Proteus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In 1966, Ferrandes et al (72) reported that cytochromes were concentrated in the mesosomal fraction of B. subtilis. As pointed out by Ryter (249), this observation was supported by circumstantial evidence such as the absence of cytochromes in membranes of Lforms of gram-positive bacteria which do not have mesosomes (327). However, as the methods for fractionation of mesosomal membranes improved, the original observation of Ferrandes et al (72) could not be reproduced.…”
Section: Chemical Composition Of Isolatedmentioning
confidence: 95%
“…In 1966, Ferrandes et al (72) reported that cytochromes were concentrated in the mesosomal fraction of B. subtilis. As pointed out by Ryter (249), this observation was supported by circumstantial evidence such as the absence of cytochromes in membranes of Lforms of gram-positive bacteria which do not have mesosomes (327). However, as the methods for fractionation of mesosomal membranes improved, the original observation of Ferrandes et al (72) could not be reproduced.…”
Section: Chemical Composition Of Isolatedmentioning
confidence: 95%
“…Thus, the Staphylococcus and Corynebacterium L forms require a medium of rather high osmotic pressure for growth, a requirement not exhibited by the Proteus L forms (Dienes and Sharp, 1956). The first two organisms contain little or no catalase and cytochromes, enzymes found in large amounts in the last (Weibull and Gyllang, 1965). One Proteus L form, strain L 9, contains considerable amounts of a typical cell-wall component, diaminopimelic acid (DAP) (W1eibull, 1958); the others, only trace amounts (AMorrison and Weibull, 1962).…”
Section: Fig 4 Section Of Amentioning
confidence: 99%